Comparison genetic diversity and population structure of four Pseudaspius leptocephalus populations in Heilongjiang River Basin based on mitochondrial COI gene - Wei, Haijun; Geng, Longwu; Shang, Xinchi; Li, Lei; Ma, Bo; Zhang, Yuyong; Li, Wang; Xu, Wei (Frontiers in Marine Science, 2023)
The Pseudaspius leptocephalus is a unique fish in the Heilongjiang River Basin and has important economic and ecological value. In the present study, the complete mitochondrial genome of P. leptocephalus were determined, and COI partial sequences of 85 individuals from Erguna river (EH), Mohe (MH), Fuyuan (FY), Hulan (HL) were used to evaluated the genetic diversity of four populations of P. leptocephalus in Heilongjiang River Basin. The mitogenome is 16,607 bp in length and contained one D-loop, 2 rRNA, 13 PCG, and 22 tRNA. 4 variable sites and 5 haplotypes were detected in 705 bp COI, and 705 bp COI exhibited a lower content of C + G (45.95 %) than A + T (54.05 %). The nucleotide diversity (π) and haplotype diversity (h) indices ranged from 0.00027 (HL) to 0.00065 (EH and FY) and from 0.192 (HL) to 0.462 (EH), respectively. The genetic distance within the population and between populations ranged from 0.0006554 to 0.0002728 and from 0.0003541 to 0.0006974, respectively. Pairwise values of FST and Nm showed that there was moderate genetic differentiation between EH population and other populations and individuals between EH population and other populations can mate randomly (0.15 > FST > 0.05, Nm > 4). Significant negative values of neutrality tests (P < 0.05) indicated that MH and FY populations may had experienced population expansion, but mismatch distribution analysis suggested that all populations have remained basically stable. These results provide strong basis for the protection and utilization of P. leptocephalus germplasm resources, and provide valuable information for the population structure and genetic diversity of P. leptocephalus.